Kreativitas Belajar Mahasiswa Ditinjau Dari Penggunaan Media Internet Dan Buku Ajar Dalam Mata Kuliah Akuntansi Perusahaan Dagang Pada Mahasiswa Pendidikan Akuntansi FKIP UMS Angkatan Tahun 2015/2016 - Dzikri Zufriansyah, Muhammad; , Drs. Muhammad Yahya, M.Si (2017)
This study was conducted in order to determine the effect of the use of internet media and textbooks to the student's creativity in an accounting class trading company in Accounting Education Guidance and Counseling Student-UMS.Year of 2015. This study uses descriptive quantitative research design. The study population numbered 252 and 146 sample taken using simple random sampling technique. The technique of collecting data using questionnaires. The data analysis technique used is Test Prerequisites (Normality Test and Test linearity) and Hypothesis (multiple regression analysis, ttest, Ftest, Test Coefficient of Determination, Relative Contribution and Contribution Effective). The results of multiple regression analysis obtained: Y = 2.932 + 0,31X1 + 1,064X2. This equation shows that the creativity of learning is affected by the use of internet media and textbooks. The conclusion is: 1) Internet Media there is no significant effect on learning creativity. Based on t test results are known tcount0.474<ttabel2.147. 2) Media textbook contained a significant impact on learning creativity. Based on the test t known tcount10,468 > t table 2.147. 3) Use of Internet media and textbooks contained a significant impact on learning creativity. Based on F test known Fcount 170.663>Ftabel 3.0593. 4) The coefficient of determination (R2) of 0705 shows the magnitude of the effect of the use of internet media and textbooks to learn creativity amounted to 70.5% while the rest influenced by other variables. Keywords: creativity in learning, internet media, textbooks.